Mitochondrial-derived peptides in energy metabolism - Merry, Troy L.; Chan, Alex; Woodhead, Jonathan S.T.; Reynolds, Joseph C.; Kumagai, Hiroshi; Kim, Su Jeong; Lee, Changhan (American Journal of Physiology - Endocrinology and Metabolism, 2020)
Mitochondrial-derived peptides (MDPs) are small bioactive peptides encoded by short open-reading frames (sORF) in mitochondrial DNA that do not necessarily have traditional hallmarks of protein-coding genes. To date, eight MDPs have been identified, all of which have been shown to have various cyto- or metaboloprotective properties. The 12S ribosomal RNA (MT-RNR1) gene harbors the sequence for MOTS-c, whereas the other seven MDPs [humanin and small humanin-like peptides (SHLP) 1-6] are encoded by the 16S ribosomal RNA gene. Here, we review the evidence that endogenous MDPs are sensitive to changes in metabolism, showing that metabolic conditions like obesity, diabetes, and aging are associated with lower circulating MDPs, whereas in humans muscle MDP expression is upregulated in response to stress that perturbs the mitochondria like exercise, some mtDNA mutation-associated diseases, and healthy aging, which potentially suggests a tissue-specific response aimed at restoring cellular or mitochondrial homeostasis. Consistent with this, treatment of rodents with humanin, MOTS-c, and SHLP2 can enhance insulin sensitivity and offer protection against a range of age-associated metabolic disorders. Furthermore, assessing how mtDNA variants alter the functions of MDPs is beginning to provide evidence that MDPs are metabolic signal transducers in humans. Taken together, MDPs appear to form an important aspect of a retrograde signaling network that communicates mitochondrial status with the wider cell and to distal tissues to modulate adaptative responses to metabolic stress. It remains to be fully determined whether the metaboloprotective properties of MDPs can be harnessed into therapies for metabolic disease.
Keywords: Animals; Energy Metabolism; Humans; Mitochondria; Mitochondrial Proteins; Peptides; Aging; Humanin; Mitochondria; Mitochondrial derived peptides; Mitokine; MOTS-c; SHLP